Organic matter in surface sediments from the Gulf of Mexico and South China Sea: Compositions, distributions and sources. Issue 1 (15th July 2017) - Wang, Cuiping; Jia, Weili; Wang, Dong; Song, Zhiguang
Abstract: Sediments from the Gulf of Mexico (GOM) and the South China Sea (SCS) were analyzed. The low δ 13 C values of pentamethylicosane (PMIs) and fatty acids (− 81.3 to − 85.2‰) were found in only the S-1 sample collected from the GOM, indicating that methanogenic archaea associated with gas hydrate formation contributed to the sediment organic matter. Principle component analysis of fatty acids suggested that similar microbial biomass was found in the S-1, S-9, O-3 and O-5 samples. However, a comparison of the alkanes, fatty acids, and alcohols indicated that the percentage of n -alkan-2-ols in the S-1 sample from the GOM was the highest, while n -alkanes and n -fatty acids were the highest percentages in other samples from the GOM and SCS. This finding suggests that microbial species or the oxidation/reduction environment of the sample site of S-1 were different from those of the other samples. The present study provides a basis for detecting gas hydrate sites on the seafloor of the SCS. Highlights: Low δ 13 C values of unsaturated fatty acids suggested archaeal bacteria contribution. 6, 10, 14-Trimethylpentadecan-ol was only detected in S-1 sample. C30 4-Methyl steranes were detected only in the samples from the SCS. Principle component analysis discriminate the microbial contributions to samples. S-1 sample associated with gas hydrate were different from the other sample.